The Influence of Operation Duration and Ischemic Time of Artificial Circulation on the Structure of Postoperative Complications in Patients after Surgical Treatment of Multivalvular Defects Combined with Coronary Pathology - Petro M. Semeniv (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To determinate the influence of the duration of artificial circulation and ischemic time on the structure of complications with one-time combined correction of lesions of two or three heart valves and myocardial revascularization and the possibility of their avoidance.Materials and methods. The work is based on a comparative analysis of the results of one-step multivalvular correction combined with coronary artery bypass grafting (CABG) in 93 patients, which was performed at the National Amosov Institute of Cardiovascular Surgery from 2014 to 2021. Depending on the tactical approaches and the sequence of surgical manipulations, the patients were divided into three groups. Group I included patients who underwent heart valve correction first and then CABG with the use of cardioplegia (n = 42), group II patients underwent CABG first and then valve correction with the use of cardioplegia (n = 36), and group III patients underwent off-pump CABG first and then correction of the heart valves (n = 15). The groups differed significantly in terms of ischemic time and artificial circulation.Results. The use of different approaches to achieve high-quality protection of the myocardium during ischemia and to minimize the impact of artificial circulation on the body by improving conditions and reducing ischemic time in the correction of multivalvular lesions and CABG showed significant advantages of the method of off-pump bypass.Conclusions. Correction of combined valvular and coronary pathology in patients with cardioplegic arrest increases the ischemic time above the critical point, which affects the occurrence of specific complications, especially acute heart failure, which significantly worsens the immediate results of surgery. Complications that occurred in the postoperative period in patients with the correction of valvular defects combined with CABG were due to prolonged cardiovascular failure. The technique proposed in the study group with off-pump bypass surgery was more effective than in groups where bypass was performed with the use of cardioplegic cardiac arrest. This technique requires more time to perform and is more technically complex, but can significantly reduce myocardial ischemic time, which, in turn, significantly reduces the incidence of heart failure and postoperative complications.